Continuos horizontal casting of small-diameter billets from waste of Br05Z5C5 - A. G. Solovej; S. R. Tchudakov; P. I. Zimonin; Yu. L. Stanjulenis (Литьë и металлургия)
The articles describes the advantages of technologic procedure of reprocessing bronze waste, developed and implemented at this enterprise.